Promotif dan Preventif Dalam Upaya Pencegahan Karies Gigi Pada Murid SD Negeri i Kayee Lheu Kabupaten Aceh Besar - Reca, Reca; Nuraskin, Cut Aja; Salfiyadi, Teuku; Rahayu, Eka Sri; Mardiah, Ainun (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Dental caries is a disease caused by the interaction between debris and plaque bacteria, diet and teeth. Dental caries tops the list of other diseases in Indonesia. The prevalence of dental disease, especially in children aged 12 years, has a tendency to increase. Prevention of caries can be done by brushing your teeth. The purpose of community service is to increase students' knowledge about how to prevent dental caries and improve students' skills in brushing their teeth properly and correctly. This activity was carried out for students of SDN I Kayee lee Kec. Aceh Besar in 2018 with a target of 30 students in class IV A. The interventions provided were in the form of counselling and accompanied by demonstrations of how to brush teeth properly and correctly, brushing teeth together. The results of the activity showed that 83% of students already knew how to prevent dental caries. It is recommended that students to be able to increase their knowledge about how to brush their teeth properly and correctly and be able to apply dental and oral health maintenance measures in an effort to prevent dental caries.